The Effect of the Group Investigation Type Cooperative Learning Model on Presentation Skills in the Topic of Ideal Gas - Silaban, Adeline; Akbar, Muhammad; Hajar, Siti; Lasmono, Paulus G. D.; Silaban, Desy C. (Kasuari: Physics Education Journal (KPEJ), 2025)
Scientific presentation is one of the essential skills that every individual should possess, particularly those involved in the fields of education and research. Classroom learning is often focused on children's ability to memorize. This study aims to determine how presentation skills use the GI type cooperative model. This study used two variables: the independent variable and the dependent variable. The independent variable was the learning model, specifically a cooperative learning model of the group investigation type. The dependent variable in this study was the ability to learn. The type of research used is descriptive qualitative, as the purpose of this study is to provide a comprehensive picture of the phenomenon. The study's results showed an average increase of 17 points, accompanied by a decrease in the standard deviation value from 5.86 to 3.64, indicating the development of presentation skills following participation in GI-type cooperative learning. The results of the normality test on the presentation ability data at the pretest stage showed that the significance value in the Kolmogorov-Smirnov test was 0.116 and in the Shapiro-Wilk test was 0.061, indicating that the pretest data did not deviate significantly from a normal distribution.